Subxiphoid-subcostal versus transthoracic thoracoscopic thymectomy: A safe and feasible approachCentral MessagePerspective - Madhuri Rao, MD; Aitua Salami, MD; Alexandria Robbins, MD; Jamee Schoephoerster, BS; Amit Bhargava, MD; Ilitch Diaz-Gutierrez, MD; Qi Wang, MS; Rafael Andrade, MD (JTCVS Techniques)
Objective: Subxiphoid-subcostal thoracoscopic thymectomy (ST) is an emerging alternative to transthoracic thoracoscopic thymectomy. Potential advantages of ST are the avoidance of intercostal incisions and visualization of both phrenic nerves in their entirety. We describe our experience with ST and compare our results to our previous experience with transthoracic thoracoscopic thymectomy. Methods: We conducted an institutional review board-exempt retrospective review of all patients who had a minimally invasive thymectomy from August 2008 to October 2021. We excluded patients with a previous sternotomy or radiological evidence of invasion into major vasculature. The ST approach involved 1 subxiphoid port for initial access, 2 subcostal ports on each side, and carbon dioxide insufflation. We used descriptive and comparative statistics on demographic, operative, and postoperative data. Results: We performed ST in 40 patients and transthoracic thoracoscopic thymectomy in 16 patients. The median age was higher in the ST group (58 years vs 34 years; P = .02). Operative data showed no significant differences in operative times, blood loss, or tumor characteristics. In the ST group, we had 2 emergency conversions for bleeding; 1 ministernotomy, and 1 sternotomy. Postoperative data showed that the ST group had fewer days with a chest tube (1 day vs 2.5 days; P = .02). There were no differences in median length of stay, tumor characteristics, final margins, major complication rate, and opioid requirements between the groups. There has been no incidence of diaphragmatic hernia and no phrenic nerve injuries or mortality in either group. Conclusions: ST is safe and has similar outcomes compared with transthoracic thoracoscopic thymectomy.